Comparative characteristics of Coordination fitness and power of middle class - Іващенко, О. В.; Шепеленко, Г. П. (Physical Education Theory and Methodology, 2014)
Purpose — to determine the sex of functional and motor fitness of students in the eighth and ninth grades. Materials and methods. In the study involved 16 girls and 14 boys grade 8, 17 and 14 girls boys 9 classes. Research results. Statistically significant differences between boys and girls 8 classes observed in tests № 10-14, describing the actual force preparedness (p <0.001). According to the results of other motor tests differences between mean values are statistically unreliable (p> 0,05). Statistically significant differences between boys and girls 9 classes observed in tests № 9-12, 14, describing the coordination and the actual force preparedness (p <0.001). According to the results of other motor tests differences between mean values are statistically unreliable (p> 0,05). Conclusions. Standardized canonical discriminant function coefficients can determine the value of the deposit outcome variables in function and demonstrates the possibility of sexual vidminostey grading students based on testing coordination and force readiness boys and girls.